2017
DOI: 10.1038/tp.2016.266
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-dose-dependent DNA methylation and expression in the nucleus accumbens identifies coordinated regulation of synaptic genes

Abstract: Alterations in DNA methylation have been associated with alcohol exposure and proposed to contribute to continued alcohol use; however, the molecular mechanisms involved remain obscure. We investigated the escalating effects of alcohol use on DNA methylation, gene expression and predicted neural effects in the nucleus accumbens of rhesus macaques that self-administered 4% alcohol for over 12 months. Using an exploratory approach to identify CpG-rich regions, followed by bisulfite sequencing, the methylation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 53 publications
7
53
0
Order By: Relevance
“…We also reported region-specific changes in mucosal tissue gene expression and microbial composition with CD (22). Additional studies using this cohort of macaques have reported suppression of intracortical bone remodeling (23) as well as gene expression and DNA methylation pattern changes in the brain associated with CD (24)(25)(26). Here, we examined the impact of CD on the transcriptional profiles and functional responses of LPLs isolated from the duodenum, jejunum, ileum, and colon in presence or absence of phorbol myristate acetate (PMA) and ionomycin stimulation.…”
supporting
confidence: 59%
“…We also reported region-specific changes in mucosal tissue gene expression and microbial composition with CD (22). Additional studies using this cohort of macaques have reported suppression of intracortical bone remodeling (23) as well as gene expression and DNA methylation pattern changes in the brain associated with CD (24)(25)(26). Here, we examined the impact of CD on the transcriptional profiles and functional responses of LPLs isolated from the duodenum, jejunum, ileum, and colon in presence or absence of phorbol myristate acetate (PMA) and ionomycin stimulation.…”
supporting
confidence: 59%
“…As noted in the previous section, gene regulation and expression by epigenetic alterations in chromatin structure, such as DNA methylation or acetylation may provide a cumulative record of genomic adaptations to chronic alcohol exposure. Using this approach, Cervera-Juanes and colleagues (2017) report that male rhesus macaques who met criteria for heavy or very heavy drinking status (Baker et al, 2014) had a greater proportion of CpG hypermethylation of synaptic genes. Importantly, the differentially regulated regions (DMRs) between heavy/very heavy and light/binge drinking monkeys were largely hypermethylated and correlated with average daily intake.…”
Section: Iii: Consequences Of Heavy Drinking On Stress Systemsmentioning
confidence: 99%
“…Importantly, the differentially regulated regions (DMRs) between heavy/very heavy and light/binge drinking monkeys were largely hypermethylated and correlated with average daily intake. Of the 17 DMRs that distinguished these two drinking phenotypes, eight were mapped to genes that regulate neurotransmitter release and receptor trafficking in a coordinated fashion (Cervera-Juanes et al, 2017). …”
Section: Iii: Consequences Of Heavy Drinking On Stress Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a plausible relationship between alcohol intake and altered one-carbon metabolism and DNA methylation (18-20), to our knowledge only one large methylome-wide association study (herein referred to as EWAS) of alcohol consumption has been conducted (21). Genes have been reported to be differentially methylated in alcohol abusers, but most evidence comes from studies that either had small sample size, were not specific to humans or were carried out using tissues other than blood (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Molecular mechanisms such as DNA methylation may underlie or enhance a predisposition to addictions and substance abuse, including alcohol drinking (23, 27, 29, 31-34).…”
Section: Introductionmentioning
confidence: 99%